Conservative management of unruptured ectopic pregnancy - Aftab, Fiza; Gani, Urba; Mufti, Samiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Ectopic pregnancy accounts for 0.5-2% of all first-trimester pregnancies and is one of the important, yet often misdiagnosed, causes of maternal death. This study aimed to determine the success rate of conservative management of unruptured ectopic pregnancy in terms of pregnancy resolution. Methods: A prospective study was conducted over a period of two years from 2020 to 2022 at the Department of Obstetrics and Gynaecology, LD Hospital of Government Medical College, Srinagar. A total of 200 patients diagnosed with unruptured ectopic pregnancy were managed with expectant or medical management, after counseling about the need of surgical options in the advent of failed treatment or rupture. Results: The cumulative success rate of conservative management of unruptured ectopic pregnancies was 70% while 30% cases had to resort to surgical intervention. Conclusions: A significant number of patients with an unruptured ectopic pregnancy can be successfully identified and treated by conservative management, thereby reducing the operative interference, morbidity and economic burden, and preserving future fertility.